Analisis Keragaman Kualitas Nutrien Berbagai Pakan Ruminansia di Wilayah Indonesia: Analysis of Variation in Nutrient Quality of Various Ruminant Feeds in Indonesia - Anggraeni Kamid, Ratu Astrid; Khotijah, Lilis; Kumalasari, Nur Rochmah (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2024)
This research aimed to evaluate the quality diversity of ruminant feeds (forages, legumes, and concentrates) from various regions in Indonesia. The material used was a database of the proximate and Van Soest analysis results of ruminant feed (grass, legumes, and concentrates) at BPMSP Bekasi, Directorate General of Animal Husbandry and Animal Health, Ministry of Agriculture for six years from 2016 to 2021. The data provided from the analysis included water content, ash content, crude protein, crude fat, crude fiber, TDN (calculation results), calcium, and Phosphorus. The data processing was done by calculating the average, standard deviation, and coefficient of variance (CV). The results showed that in the grass, the lowest CV for the dry matter was 4.67%, namely elephant grass, while the lowest CV TDN was for Setaria grass at 5.81%, brachiaria grass at 6.15% and king grass at 9.03%. Meanwhile, the test parameters for crude protein and crude fiber have CV values ​​above 10%. On Legumes, it can be seen that the lowest CV in TDN was 8.16% in Gamal 10.64% in Indigofera, and 11.10% in Turi. Meanwhile, in dry matter parameters, crude protein, crude fiber, calcium, and Phosphorus have a CV value above 10%. Most of the CV values ​​for ruminant feed are above 10%. It can be concluded that the test data on ruminant feed types has a high level of variation, and there may be a diversity. Key words: data laboratory analysis, feed quality, ruminant feed